Does Prophylactic Administration of TXA Reduce Mean Operative Time and Postoperative Blood Loss in Posterior Approach Lumbar Spinal Fusion Surgery Performed for Degenerative Spinal Disease?. Issue 7 (August 2019) - Larson, Evan; Evans, Tyler; Long, Jake; Gannon, Emmett; Lyden, Elizabeth; Cornett, Chris
Abstract : Study Design: This is a level III retrospective cohort study. Objective: To investigate association between prophylactic tranexamic acid (TXA) administration before 1 and 2-level posterior lumbar interbody fusion operations and perioperative blood loss (including intraoperative blood loss and postoperative drain output), mean operative time, postoperative transfusion, and postoperative venous thromboembolic events. Summary of Background Data: TXA is a systemic antifibrinolytic that competitively inhibits lysine binding sites on plasminogen, reversibly blocking its binding to fibrin and impeding fibrinolysis and clot degradation. TXA's role in routine spinal surgery remains poorly described. Most spinal literature on perioperative TXA administration has considered operations performed for major adult and pediatric spinal deformity. Methods: Two groups, a study group composed of 75 patients who underwent 1 and 2-level posterior lumbar interbody fusion operations for degenerative indications who received TXA before the start of the procedure, and a control group composed of 75 patients who underwent similar surgeries for the same indications and did not receive TXA preoperatively, were retrospectively enrolled. Demographic, laboratory, and surgical data were collected and analyzed. Results: No statistically significant differences were found between groups with respect to surgery type, home anticoagulation, postoperative anticoagulation, preoperative hemoglobin and hematocrit, estimated intraoperative blood loss, postoperative day 2 drain output, postoperative day 3 drain output, rate of postoperative transfusion, and rate of postoperative thromboembolic events. Statistically significant reductions were noted in the TXA group with regards to postoperative day 1 drain output ( P <0.0041), total postoperative drain output ( P =0.027), and mean surgical time ( P <0.0001). Conclusions: In the present study, perioperative TXA administration was associated with reduced postoperative drain output and surgical time. Further higher-level studies are required to investigate the safety and utility of TXA's routine use in 1 and 2-level posterior lumbar fusion operations performed for degenerative indications.